Pseudo porphyria or porphyria cutanea tarda? - Modesto dos Santos, Vitorino (Revista de Gastroenterología del Perú, 2018)
Manuscripts about pseudoporphyria (PP) and porphyria cutanea tarda (PCT) are commented here, emphasizing some gastroenterological relationships and possible diagnostic challenges or misdiagnosis, in special for daily practice of primary health care workers. Batrani et al. described PP associated with the use of imatinib and manifested by bullae, erosions, scarring and milia on the dorsum of hands and feet, in absence of photosensitivity (1). Biopsy sample showed subepidermal blister, dermal festooning of papillae and thickened vessels; and the level of urinary porphyrin was within the normal range (1). Imatinib has been also associated with PCT; however, in this patient the diagnosis was consistent with PP (1). Peláez- Castro et al. reported the first Peruvian case of PP in a hemodialytic woman with facial hyperpigmentation, bilateral bullae on the fingers, and some crusts on the dorsum of hands (2). Biopsy study revealed sub epidermal blisters, with dermal festooning and mild lymphocytic infiltrate; however, the normal profiles of porphyrins allowed confirm the diagnosis of PP (2). This condition is related to renal failure and hemodialysis, non-steroidal anti-inflammatory drugs, furosemide, retinoids, sulphonamides, tetracyclines, dapsone, and nalidixic acid (1,2). Hypertrichosis, hyperpigmentation, calcifications and sclerodermoid lesions are uncommon in PP; however, clinical, histopathological and immunofluorescence features can mimic PCT (1). Therefore, normal urinary and plasmatic porphyrins are mandatory for diagnosis of PP (1,2).